2016
DOI: 10.1557/jmr.2016.418
|View full text |Cite
|
Sign up to set email alerts
|

New insights on ion track morphology in pyrochlores by aberration corrected scanning transmission electron microscopy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Thus, these calculations show that strain could also be used to tailor oxygen conductivity in these materials, like fluorite and perovskite materials. STEM studies are being increasingly utilized for analyzing ion track morphology ( Lang et al, 2015 ; Sachan et al, 2017a ; Sachan et al, 2017b ).…”
Section: Structure Analysis From Real-space Imagingmentioning
confidence: 99%
“…Thus, these calculations show that strain could also be used to tailor oxygen conductivity in these materials, like fluorite and perovskite materials. STEM studies are being increasingly utilized for analyzing ion track morphology ( Lang et al, 2015 ; Sachan et al, 2017a ; Sachan et al, 2017b ).…”
Section: Structure Analysis From Real-space Imagingmentioning
confidence: 99%
“…For example, ion tracks, that is, damage zones of several nanometers in diameter, form along the ion trajectory in many materials. [24][25][26][27][28] In most cases, the ion tracks are cylindrical and amorphous. [24][25][26][27][28] However, it was found that the ion track morphology in rutile TiO 2 and MoS 2 is variable as a function of the ion path length.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] In most cases, the ion tracks are cylindrical and amorphous. [24][25][26][27][28] However, it was found that the ion track morphology in rutile TiO 2 and MoS 2 is variable as a function of the ion path length. 29,30 Another feature of ion tracks in these two materials is that they exhibit some porosity as evidenced by Fresnel contrast observed by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…These nonequilibrium processes enable the formation of various metastable atomically disordered phases that, due to the lack of distinct atomic sites for cations, exhibit unique physical properties and potential novel functionalities. For instance, atomically disordered defect-fluorite phases in A 2 B 2 O 7 structured oxides are reported to have high radiation tolerance, , as well as fast ionic conductivity. The spinel phase ferrites (AFe 2 O 4 ) exhibit unusual magnetic properties through cation antiferromagnetic coupling . The heavily doped defective structures show high-temperature superconductivity characteristics because of the lattice atom substitution and the formation of Cooper pairs. , Among various routes to achieve such phase transformation, energetic electron-irradiation (e-irradiation) is seen as an effective technique, especially for nanoscale devices with local preferential phase transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation using the scanning e-beam in a STEM is a useful extrapolation of the same technique, which, in principle, achieves subnanometer-level nanofabrication and advances interface engineering science by creating epitaxial complex nanostructures. ,, The present work follows the same direction and focusses on the spatially controlled phase transformation of amorphous phase nanochannels embedded in pyrochlore-structured A 2 B 2 O 7 matrix. The choice of A 2 B 2 O 7 structured complex oxides is based on their unique atomic structure providing potential applications, such as fast ionic conductors, topological insulators, and matrix for immobilization of nuclear waste or thermal barrier coatings. , ,, These materials show a remarkable capability of disordering by atomic rearrangement under high-energy ion irradiation and preferentially transform to a disordered crystalline defect-fluorite phase or an amorphous phase under specific conditions. …”
Section: Introductionmentioning
confidence: 99%